Effect of PrekotAc on pressure drop and particle penetration in filtration system - Andenan, Nurnadia (2015)
The effect of a filter aids known as PrekotAC on pressure drop and particle penetration in a filtration system with varying filtration velocity of 1 to 5 m/min was evaluated in this study. The PrekotAC is a combination of PrekotTM and activated carbon mixed in different weight composition. The result showed that the pressure drop across the fabric media decreases with the addition of PrekotTM in the PrekotAC admixture due to its wide range of non-uniform particle size ditribution that gives higher porosity of filter cake during filtration process. The study also showed that the total particle penetration through the fabric media was proportionally related to addition of PrekotTM in the PrekotAC admixture under a constant material loading. The study suggests that the addition of PrekotTM in the formulation of filter aids significantly affect both pressure drop and penetration of the fabric filter media.